ANALISIS PARTISIPASI SISWA DALAM DISKUSI KELOMPOK KELAS V DI SD MUHAMMADIYAH 1 LIMBOTO - Rizka Abilla Lasoa; Abd. Hamid Isa; Fandi H. Binggo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student participation in group discussions is an important indicator for creating active and collaborative learning in elementary schools. In fifth grade students at Muhammadiyah 1 Limboto Elementary School, there is still an imbalance in participation, where only a small number of students actively dominate discussions, while the majority tend to be passive due to internal factors such as low self-confidence, limited speaking skills, and differences in understanding of the material, as well as external factors such as group dynamics and teacher management. This study aims to analyze student participation in group discussions and the factors that influence it. The study used a case study approach with data collection techniques of observation, interviews, and documentation. Data analysis was conducted descriptively qualitatively with the stages of data reduction, data presentation, and drawing conclusions/verification, as well as triangulation to ensure data validity. The results showed that student participation was not optimal, with low verbal levels and nonverbal/social dominance, influenced by the interaction of internal and external factors. Teacher efforts were effective through role allocation, creating a safe atmosphere, and motivation, although they need to be improved for equitable involvement. Student participation in fifth grade students at Muhammadiyah 1 Limboto Elementary School reflects psychological and social challenges that can be overcome with a systematic and inclusive teacher facilitative approach.